2021
DOI: 10.1111/ene.14899
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in young adults with acute ischemic stroke undergoing endovascular thrombectomy: A real‐world multicenter experience

Abstract: are co-first authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
4
12
2
Order By: Relevance
“…Young patients were associated with better clinical outcomes, which was consistent with existing literature [ 10 , 11 , 28 , 29 ]. For example, 40.78% (62/152) of young patients with stroke achieved favorable outcomes at 90 days, resulting in a difference of 11.43% (95% CI 2.65–20.22) compared with old patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Young patients were associated with better clinical outcomes, which was consistent with existing literature [ 10 , 11 , 28 , 29 ]. For example, 40.78% (62/152) of young patients with stroke achieved favorable outcomes at 90 days, resulting in a difference of 11.43% (95% CI 2.65–20.22) compared with old patients.…”
Section: Discussionsupporting
confidence: 91%
“…3 ) also indicated that young adults had a better prognosis. In a real-world multicenter experience, 66.20% of young patients (aged < 50 years) who underwent EVT because of large artery occlusion achieved favorable outcomes and 4.70% of the patients died [ 11 ]. For these patients, the rate of favorable clinical outcome (mRS 0–2) at 3 months was higher (61.00% vs. 38.80%) and mortality was lower (6.80% vs. 31.90%) than in old patients according to the MR CLEAN Registry [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arterial dissection was detected in 17.8% of our patient cohort, and did not significantly differ between young female and male AIS patients. This percentage lies within the range of 16% and 21.5% reported in AIS patients under 50 years of age undergoing MT in the MR CLEAN Registry Study and in a recently published multicenter cohort study, respectively [ 7 , 8 ].…”
Section: Discussionsupporting
confidence: 69%
“…We recently read the original article by Leonard Leong-Litt Yeo et al [1], published in the European Journal of Neurology. Their study enrolled 275 patients with acute ischemic stroke, aged ≤50 years, who underwent endovascular thrombectomy in 10 comprehensive stroke centers across four different countries.…”
Section: E T T E R S T O T H E E D I T O R Younger Adults and Endovas...mentioning
confidence: 99%